The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.est.5b02049
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Potency of Microcystin, an Important Water-Polluting Cyanobacterial Toxin

Abstract: Microcystins (MCs) are primarily hepatotoxins produced by cyanobacteria and are responsible for intoxication in humans and animals. There are many incidents of chronic exposure to MCs, which have been attributed to the inappropriate treatment of water supplies or contaminated food. Using RAW 264.7 macrophages, we showed the potency of microcystin-LR (MC-LR) to stimulate production of pro-inflammatory cytokines (tumor necrosis factor α and interleukin-6) as a consequence of fast nuclear factor κB and nitrogen-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 56 publications
(112 reference statements)
2
31
1
Order By: Relevance
“…Increased phosphorylation was observed in the human HL7702 liver cell line after 48-h exposure to 10 µM MC-LR [72], but not in human HL1-hT1 adult liver stem cells exposed to 1 µM [56], despite toxin uptake was documented in both studies. Elevated P-ERK1/2 levels were additionally reported by Adamovsky et al [31] in murine RAW 264.7 macrophages after 30-min exposure to 1 µM MC-LR, but probably triggered via interactions of the toxin with membrane receptors, independently of MC-LR cellular uptake and inhibition of PPs.…”
Section: Discussionsupporting
confidence: 52%
“…Increased phosphorylation was observed in the human HL7702 liver cell line after 48-h exposure to 10 µM MC-LR [72], but not in human HL1-hT1 adult liver stem cells exposed to 1 µM [56], despite toxin uptake was documented in both studies. Elevated P-ERK1/2 levels were additionally reported by Adamovsky et al [31] in murine RAW 264.7 macrophages after 30-min exposure to 1 µM MC-LR, but probably triggered via interactions of the toxin with membrane receptors, independently of MC-LR cellular uptake and inhibition of PPs.…”
Section: Discussionsupporting
confidence: 52%
“…MC-LR at the lowest dose (1 ng/mL) increased the mRNA expression of IL-6, whereas the highest dose markedly diminished the expression of this cytokine. In contrast, the production of IL-6 in macrophages (RAW 264.7 cell line) was only slightly induced at the highest concentration (1000 nM) of MC-LR (Adamovsky et al, 2015). The evidence of disturbance of IL-6 potentially indicates the negative effect of MC-LR on the inflammatory reaction after a 6-h treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies on MC‐LR (Adamovsky et al, ; Adegoke, Wang, Machebe, Adeniran, et al, ; Adegoke, Wang, Machebe, Wang, et al, ) indicated that MC‐LR elicit its toxic effects via TLR4 signaling pathways. Therefore, the TLR4 signaling pathway was made the target for amelioration and attenuation of MC‐LR toxicity in this study.…”
Section: Discussionmentioning
confidence: 98%
“…According to Huggins et al (), the TLRs, including TLR4, have been shown to play a crucial role in inflammatory diseases. MC‐LR has been reported to induce inflammation in bovine Sertoli cells (Adegoke, Wang, Machebe, Wang, et al, ), in human umbilical vein endothelial cells (Shi, Zhou, & Zhang, ) and activates TLRs, particularly TLR4 in the RAW 264.7 cell line (Adamovsky et al, ). Meanwhile, all TLR signaling pathways culminate in activation of the transcription factor nuclear factor‐kappaB (NF‐κB), which controls the expression of an array of inflammatory cytokine genes (Taro & Shizuo, ).…”
Section: Introductionmentioning
confidence: 99%